The University of Michigan Pocket Guide for Clinician-in-training Assessment of the Neuropsychiatric Symptoms of Dementia - Katherin Rockefeller; Mary Blazek; Janet Kavanagh; Helen Kales (MedEdPORTAL, 2013)
Abstract Introduction In addition to cognitive deficits, patients with dementia often experience behavioral and psychological symptoms, also known as neuropsychiatric symptoms (NPS), which is a term that covers a heterogeneous group of symptoms (i.e., mood disorders, apathy, anxiety, psychotic disorders, psychomotor agitation, aggression, sleep disturbances, eating problems, and inappropriate behavior). The management of NPS tends to be one of the most challenging aspects of dementia care, increasing both caregiver burden and the likelihood of institutionalization. A crucial step in the development of a targeted nonpharmacological intervention is conducting a comprehensive assessment of the patient's distressing NPS. The University of Michigan Pocket Guide for Assessment of the Neuropsychiatric Symptoms of Dementia aims to highlight the complex and often overlooked assessment of NPS and responds to the growing demand for clinicians educated in geriatric mental health treatment. Methods The pocket guide provides an easy-to-reference outline of NPS assessment. This assessment is divided into four parts: (1) screening for behavioral and psychological symptoms, (2) defining the character, context, and consequences of one distressing symptom — the target symptom, (3) investigating the possible causes of the target symptom, and (4) accurately documenting NPS to assist with longitudinal assessment. It can be integrated into curricula on dementia care, particularly through its application to case examples, then conveniently referenced before, during, and after patient encounters. The pocket guide is designed for clinicians-in-training, including medical and psychiatric residents, fellows, and nurses. Results The pocket guide was first introduced to a group of 22 resident, fellow, and nursing trainees as well as medical and nursing professionals as part of the University of Michigan Brainstorming Workshop for Non-pharmacological Interventions in Behavioral Disturbances in Dementia. Before receiving a copy of the pocket guide, each participant completed a baseline survey to measure experience and confidence in NPS assessment and potential use of the pocket guide. Seventeen of the 22 participants completed this survey. Twelve (71%) of the 17 participants believed a pocket guide would be useful in their practice. Two months later, a follow-up survey was administered and completed by 13 participants. Six out of 13 respondents (46%) read or referenced the Pocket Guide after the brainstorming session. Of these six individuals, 4 (67%) found it “very useful” and 2 (33%) found it “moderately useful.” Regarding use, five (83%) found it “very easy to use” and one (17%) found it “somewhat easy to use.” Five (83%) of those who read or referenced the pocket guide believed it improved their confidence. Discussion Overall, our experience with the pocket guide suggest that training in NPS recognition and assessment is an important part of developing a workforce capable of managing dementia patients. Quantitative and qualitative feedback indicates that the pocket guide can serve as an evidence-based teaching and clinical resource that contributes to this effort. We plan to continue to incorporate the pocket guide in the yearly brainstorming workshop in hopes that more clinicians-in-training will be exposed to and provide feedback on it to direct future improvements. This feedback and future revisions may also inform the creation of a subsequent pocket guide designed to inform the management of NPS.